STUDI KRITIS MINUMAN TEH KOMBUCHA: MANFAAT BAGI KESEHATAN, KADAR ALKOHOL DAN SERTIFIKASI HALAL - Priyono Priyono; Dody Riswanto (International Journal Mathla’ul Anwar of Halal Issues, 2021)
Kombucha tea has become a trendy drink and is in demand by consumers because it has many health benefits. However, the fermentation of kombucha also produces ethanol or alcohol. Halal status has become a global issue. No exception for kombucha tea products. The purpose of this study was to examine the health benefits, alcohol content and halal certification of kombucha tea. The method approach used is the literature study method. The results of the study indicate that kombucha tea is a fermented drink that has an effect on the health of the human body by having biological activities such as antioxidants, antimicrobials, antidiabetic, anticancer, hepaprotective and anti-inflammatory properties. The alcohol content in kombucha tea can be consistently below 0.5% if the kombucha manufacture meets certain standard and standard processes. Kombucha tea in Indonesia has products that have received halal certification.